Utilization of Artificial Intelligence in English Language Teaching (Innovation to Improve Language Skills) - Risma Fahrul Amin; Ummal Khoiriyah (Hikamatzu | Journal of Multidisciplinary, 2024)
This study explores the transformative role of Artificial Intelligence (AI) in English Language Teaching (ELT), focusing on its innovations, opportunities, and challenges. AI technologies such as adaptive learning platforms, chatbots, and writing assistants have revolutionized language education by offering personalized learning experiences, enhancing interactive skill development, and improving assessment processes through real-time feedback and data-driven insights. However, the study also highlights challenges, including access disparities, ethical concerns related to data privacy, and the limitations of AI in addressing cultural and contextual nuances of language. Drawing from recent literature, the analysis underscores the importance of integrating AI as a complementary tool rather than a replacement for human educators, emphasizing the irreplaceable role of teachers in fostering emotional connections and cultural understanding. This study concludes that the effective and equitable adoption of AI in ELT requires thoughtful implementation, bridging technological advancements with human expertise to create a holistic and inclusive learning environment